ANALISIS KETERLAMBATAN BONGKAR MUATAN DI MV. RASUNA BARUNA - M. Adhan Febriansa Saputra; Egbert Edward Djajasasana; Abd. Majid (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2026)
The cargo discharging process is a primary operational activity that determines berthing time efficiency and vessel operating costs. On MV. Rasuna Baruna, delays in cargo discharging still occur, affecting sailing schedules and ship productivity. This study aims to identify the factors causing the delays and to formulate appropriate corrective measures. This research employed a descriptive qualitative method. Data were collected through direct onboard observation, semi-structured interviews with the Master, Chief Officer, crane operators/technicians, port officers and stevedoring company (PBM), as well as documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing to obtain a factual and systematic description. The results indicate that the delays were mainly caused by technical problems of the deck crane, such as slewing bearing wear, decreased hydraulic pressure, and wire grab damage. Other contributing factors include suboptimal preventive maintenance and less effective operational coordination. The measures taken include improving routine maintenance, replacing worn components, optimizing officers' supervision, and strengthening coordination with the port and stevedoring company to enhance discharging productivity. Keywords: cargo discharging delay, deck crane, maintenance, productivity, operational coordination.